2021
DOI: 10.1007/s11250-021-02988-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen use efficiency and soil chemical composition in small-scale dairy systems

Abstract: In dairy production systems, the efficient use of resources is required to guarantee its sustainability. Worldwide, the efficiency of feed utilization and its effects have been widely studied. However, few studies have quantified animal nitrogen use and its corresponding soil contribution in small-scale production systems. Therefore, this study aimed to determine the efficiency of feed utilization and quantify the soil chemical composition in small-scale production systems using two different feeding strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…CP and N consumption was numerically lower for T3 with inclusion of 6 kg of sugarcane top silage, which was reflected in the excretion of N from the manure and the efficiency of feed utilization. In this regard, a study carried out by Pozo-Leyva et al (2021a) in central Mexico with cows fed mixed grasses documented N intake of 344.9 g/cow/day with excretion of N in manure of 251.3 g/cow/day, higher than that reported by Aarons et al (2017), carried out in the USA, of 19.4%. This indicates that greater consumption of N does not automatically translate into an increase in milk production, but it does influence the efficiency of feed utilization, as found in this study, since the values reported here are within the range of previous research, between 11 and 39%, documented by Aarons et al (2017).…”
Section: Chemical Composition Of Feedmentioning
confidence: 55%
“…CP and N consumption was numerically lower for T3 with inclusion of 6 kg of sugarcane top silage, which was reflected in the excretion of N from the manure and the efficiency of feed utilization. In this regard, a study carried out by Pozo-Leyva et al (2021a) in central Mexico with cows fed mixed grasses documented N intake of 344.9 g/cow/day with excretion of N in manure of 251.3 g/cow/day, higher than that reported by Aarons et al (2017), carried out in the USA, of 19.4%. This indicates that greater consumption of N does not automatically translate into an increase in milk production, but it does influence the efficiency of feed utilization, as found in this study, since the values reported here are within the range of previous research, between 11 and 39%, documented by Aarons et al (2017).…”
Section: Chemical Composition Of Feedmentioning
confidence: 55%